2000
DOI: 10.1103/physreve.62.5648
|View full text |Cite
|
Sign up to set email alerts
|

Long-wavelength limit of the dynamical local-field factor and dynamical conductivity of a two-component plasma

Abstract: A systematic approach to the optical conductivity is given within a dielectric function formalism. The response function as well as the dynamical local-field factor G(k-->,omega) of an electron-ion plasma can be expressed in terms of determinants of equilibrium correlation functions which allow for a perturbative treatment. The dynamical collision frequency nu(omega)=-iomega(2)(pl)G(0,omega)/omega for fully ionized weakly coupled plasmas is evaluated in the low-density limit. A renormalization function is give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
217
1
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(228 citation statements)
references
References 61 publications
5
217
1
5
Order By: Relevance
“…which agrees with (18). Therefore, we have shown that the dynamical local field (36) from the response function (33) leads to the same compressibility (19).…”
Section: Compressibility Sum Rulesupporting
confidence: 73%
See 2 more Smart Citations
“…which agrees with (18). Therefore, we have shown that the dynamical local field (36) from the response function (33) leads to the same compressibility (19).…”
Section: Compressibility Sum Rulesupporting
confidence: 73%
“…Therefore we have derived a dynamical response function and a local field which shows in the static limit the correct compressibility (18). This compressibility formulae (18) can be checked alternatively by calculating explicitly the frequency integral in (19)…”
Section: Compressibility Sum Rulementioning
confidence: 99%
See 1 more Smart Citation
“…As there are no independent tests of the various models [30] presently available, this experimental method will provide such a test by determining independently the electron temperature simultaneously with plasmon measurements.…”
mentioning
confidence: 99%
“…С помощью уравнений этого пункта в приведенный статистический оператор можно включить улучшенные выражения для диэлектрической функции [46], [47] или прямые выражения ДСФ в сильно коррелированной двух-или более компонент-ной плазме [48], [49]. (44) атома в многоча-стичном плазменном окружении с известными результатами.…”
Section: пертурбативное разложение основного кинетического уравненияunclassified